Appreciation of the Educational Role of the Nurse on the Inhabitants of a Community - Paulin Garcia, Cecilia (Universidad de Sonora, 2020)
Introduction: Health education is one of the most powerful desires that are used to struggle for equality and attain a healthy population with autonomy and capacity of election, where the nursing professional has a pivotal role. Objective: Explore the perception of the users of a health center about the role of the nurse in health education (EpS, by its acronym in Spanish). Methodology: Qualitative study based on the Grounded Theory carried out in a health center of a community located in Pie de Gallo, Santa Rosa Jáuregui, State of Querétaro. Data collection was made through a semi-structured interview in 2 focus groups. Ethical principles of the Council for International Organizations of Medical Sciences were respected. Results: Twenty (20) users (men and women) were interviewed. Three (3) categories of assessments were obtained, namely: a. Attitude of the nurse toward the users, b. Nursing care, and c. Additional findings. Conclusions: While the main functions of the personnel within the hospital are identified, it is necessary to go into more depth in the education area within health promotion.